2021
DOI: 10.3389/fcell.2021.648279
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Novel Signature With Nine Hepatitis C Virus-Induced Genes in Hepatic Cancer by Mining GEO and TCGA Databases

Abstract: BackgroundHepatitis C virus-induced genes (HCVIGs) play a critical role in regulating tumor development in hepatic cancer. The role of HCVIGs in hepatic cancer remains unknown. This study aimed to construct a prognostic signature and assess the value of the risk model for predicting the prognosis of hepatic cancer.MethodsDifferentially expressed HCVIGs were identified in hepatic cancer data from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases using the library (“limma”) package o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Further, bioinformatics, which is an emerging approach based on genomics and statistics, can be used to find new predictive information ( Berhane et al, 2016 ; Tai et al, 2019 ). Wei et al recently reported a nine-HCV related gene signature for predicting the overall survival of HCC, based on Gene Expression Omnibus (GEO) and TCGA databases ( Wei et al, 2021 ). Liu et al explored the prognosis value of the mRNA expression-based stemness index (mRNAsi) in HCC, and constructed a new three-gene signature with mRNAsi, based on TCGA and ICGC databases ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, bioinformatics, which is an emerging approach based on genomics and statistics, can be used to find new predictive information ( Berhane et al, 2016 ; Tai et al, 2019 ). Wei et al recently reported a nine-HCV related gene signature for predicting the overall survival of HCC, based on Gene Expression Omnibus (GEO) and TCGA databases ( Wei et al, 2021 ). Liu et al explored the prognosis value of the mRNA expression-based stemness index (mRNAsi) in HCC, and constructed a new three-gene signature with mRNAsi, based on TCGA and ICGC databases ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic values of these seven key genes in OSCC or other human diseases have been investigated. For example, a previous study established a signature using nine hepatitis C virus-induced genes including FAM72D, which could better predict the prognosis of hepatic cancer and also provide a novel way to investigate the potential mechanism of HCVIGs in this disease (37). Hu et al found the downregulation of COL27A1 in poor segmental congenital scoliosis (38), and Laura et al revealed a steel syndrome patient due to the compound heterozygous COL27A1 mutations in the eye (39).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, KEGG enrichment showed DEGs (between the EA stage and the C stage, and between the EA stage and the LA stage) were enriched in Coronavirus disease —COVID-19, Influenza A, Hepatitis C and Measles pathways, implying Coronavirus [ 54 ], Alphainfluenzavirus influenzae [ 55 ], Hepatitis C virus [ 56 ] and Measles morbillivirus also up regulated these genes during infection and had shared pathogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%